EXPERIENCE OF USING TELEMEDICINE TOOLS TO PROVIDE MEDICAL CARE IN THE TERRITORY OF DONETSK REGION DURING MARTIAL LAW IN UKRAINE - Oleksandr Heiko; Taras Gutor (Acta Medica Leopoliensia)
Aim of the study is the analysis of medical care provision to the population of Donetsk region using telecommu-nications means.